“Now once again this idea of yours (…) how does it sound when I say that?” – Changing the perspective: how coach’s questioning practices elicit self-reflecting processes in clients - Moos, Chantal; Spranz-Fogasy, Thomas (Frontiers in Psychology, 2024)
Drawing upon the transformative power of questions, the paper investigates questioning sequences from authentic coaching data to examine the systematic use of a particular succession of formulation and question and its impact on inviting self-reflection processes in the client and eliciting change. The object of investigation in this paper are therefore questioning sequences in which a coach asks a question immediately after a rephrasing or relocating action, prompting the client to respond in an explicit or implicit way. The coach hereby shifts the focus to a hypothetical scenario, prompting the client to change her perspective on the matter and reflect on her own statements, ideas and attitudes from an outside perspective. The paper aims to contribute to closing the research gap of the change potential of reflection-stimulating action techniques used by coaches, by investigating one of many ways of how questions can be powerful tools to invite a change of perspective for the client. The study focuses on one coaching process consisting of three sessions between a female coach and a female client, utilizing a single case study approach. The data collection was part of the interdisciplinary project "Questioning Sequences in Coaching" (QueSCo: https://questions-in-coaching.aau.at/), comprising 14 authentic coaching processes. The analysis follows Peräkylä's (2019) Transformative Sequences model, examining the first position including the formulation and the subsequent question, the client's response, and the coach's reaction to the response. On a practical level, the main purpose of this paper is not to contribute to the many ways practical literature recommends coaches how to do their work and how to ask questions, but rather to show in what ways the elicitation of self-reflection processes in clients has been achieved by other coaches in authentic coaching sessions.